[BP.07.05] ASSOCIATION BETWEEN URIC ACID AND CARDIAC, VASCULAR AND RENAL TARGET ORGAN DAMAGE IN HYPERTENSIVES SUBJECTS. (September 2017) - Maloberti, A.; Varrenti, M.; Triglione, N.; Occhi, L.; Panzeri, F.; Alloni, M.; Giupponi, L.; Vallerio, P.; Casati, M.; Grassi, G.; Mancia, G.; Giannattasio, C.
Abstract : Objective: To date no definitive results exist about the relationship of Serum Uric Acid (SUA) and Target Organ Damage (TOD) in hypertensives subjects (HT). We sought to determine if such an association exist between SUA and subclinical cardiac, vascular and renal alterations in HT. Design and method: We enrolled 632 consecutive outpatients, followed by the Hypertension Unit of S. Gerardo Hospital (Monza, Italy) affected by essential HT. We evaluated anamnestic data, clinical Blood Pressure (BP) and laboratory data as well as TOD with cardiac echocardiography (both as Left Ventricular Mass Index – LMVI and diastolic function – E/A), carotid ultrasound (Intima Media Thickness – IMT), arterial stiffness (Pulse Wave Velocity – PWV) and renal function analysis (creatinine and microalbumiuria). Results: Mean age was 53.4 ± 12.7 years, Systolic and Diastolic BP (SBP/DBP) were 140.5 ± 18.8 and 85.1 ± 13.1 mmHg and SUA was 5.2 ± 1.4 mg/dL. Regarding TOD mean LVMI was 109.6 ± 31.4 g/m 2, IMT 0.71 ± 0.1 mm, PWV 8.5 ± 2.2 m/s, while creatinine and microalbuminuria were 0.8 ± 0.2 mg/dL and 25.4 ± 126.1 mg/24 h respectively. When subjects were divided into high and low SUA group (depending on the median SUA of 5.2 mg/dL), with similar age and BP values the first group showed significantly higher values of metabolic index (BMI: 27.9 ± 4.1 vs 25.7 ± 4.1 kg/m 2 ; HDL chol: 49.8 ± 13.1 vs 56.8 ± 14.1 mg/dL; triglicerides: 136.1 ± 81.9 vs 104.2 ± 58.1 mg/dL; glucose: 95.4 ± 27.4 vs 86.4 ± 18.2 mg/dL, p < 0.01 for all), LVMI (117.1 ± 32.8 vs 102.1 ± 28.1 g/m 2, p < 0.01), IMT (0.73 ± 0.1 vs 0.70 ± 0.1, p = 0.04), PWV (8.8 ± 2.4 vs 8.3 ± 2.1 m/s, p = 0.01) and creatinine (0.9 ± 0.2 vs 0.7 ± 0.1 mg/dL, p < 0.01) and lower E/A (1, 0 ± 0.3 vs 1.1 ± 0.3, p < 0.01). SUA showed significant correlation with sex (r = -0.41, p < 0.01), age (r = 0.12, p = 0.01), BMI (r = 0.33, p < 0.01), SBP (r = 0.10, p < 0.01), HDL chol (r = -0.29, p < 0.01), triglicerides (r = 0.34, p < 0.01), glucose (r = 0.21, p < 0.01), creatinine (r = 0.42, p < 0.01), IMT (r = 0.12, p < 0.01), LVMI (r = 0.24, p < 0.01) and E/A (r = -0.15, p < 0.01). Regarding TOD only creatinine presents SUA as as significant determinant in logistic regression analysis with age, sex, BMI, HDL chol, triglicerides and glucose as covariates. Conclusions: In HT, SUA values correlate with metabolic derangements and with cardiac, vascular and renal TOD. The most significant correlation is with renal damage.